Differentiability of Fractional Integrals Whose Kernels Contain Fractional Brownian Motions - Krvavich, Yu. V.; Mishura, Yu. S. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We prove the stochastic Fubini theorem for Wiener integrals with respect to fractional Brownian motions. By using this theorem, we establish conditions for the mean-square and pathwise differentiability of fractional integrals whose kernels contain fractional Brownian motions.